Synod diecezjalny - narzędziem odnowy Kościoła partykularnego - Dyduch, Jan (Prawo Kanoniczne, 1997)
On March 19, 1997, an instruction entitled ‘De Synodis Dioecesanis Agendis‘ was issued jointly by the Congregation for Bishops and the Congregation for Evangelization of Peoples. This Instruction is based on the regulations of the Code of Canon Law published in 1983. In the light of the new Instruction, a Diocesan Synod is to be an instrument of renewal of religious life, pastoral ministry and of the particular Church Law. The entire community of Gods People should be envolved in the works of a Diocesan Synod: its priests, the religious and the laity. They should participate in its works on all stages - in praparations, deliberations and in fulfilment of the resolutions. A Diocesan Synod, understood like this, has the pastoral character and its legislative function is utilized for the pastoral ministry. While a Synod is in session, the Diocesan bishop is the only legislator; other participants -through their advisory voice - take part in preparing the synodal law.